PELAKSANAAN POS BANTUAN HUKUM ; RELEVANSINYA DENGAN HAK ASASI MANUSIA - Rosida Diani; Oktavia; Sela Angraini; Husnul Arifin (Justici, 2026)
Legal aid posts are one of the government's efforts to provide opportunities for every citizen to access legal aid. In its implementation, legal aid posts are now available at village offices, one of which is in the Kebun Bunga sub-district. This study uses an empirical research method with primary data obtained from interviews and secondary data obtained from primary legal materials in the form of laws and regulations, research results and literature related to the subject matter. From the results of the study, it was found that the implementation of the legal aid post most widely used in the Kebun Bunga sub-district office is mediation. The mediation process is carried out by the village head, assisted by the village secretary, Babinsa, and village staff. There are several inhibiting factors in the implementation of mediation at the Kebun Bunga sub-district office, namely resolving problems between neighbors involving emotions, a sense of prestige and long-standing resentment so that it is difficult to find an agreement, the level of education of the parties, the results of the mediation are not binding, and the difficulty of bringing the parties together due to time.